Accessibility of Tourist Offer in Republic of Croatia to People with Disabilities - GREGORIC, Marina; SKRYL, Tatiana V.; DRK, Katarina (Journal of Environmental Management and Tourism; Vol 10 No 4 (2019): JEMT Volume X Issue 4(36) Summer 2019, 2019)
The aim of the research paper is to identify the need of adaptation of tourist facilities to people with disabilities in Republic of Croatia as a tourist destination. Tourists and travellers with disabilities want to be equal members of our community and enjoy all tourist facilities just like other healthy people, although they are often restricted due to the inadequacy of tourist facilities. The paper analyses different tourist offers, amenities and infrastructure in order to assess its level of adaptation to people with disabilities in the Republic of Croatia. Research methods carried in this paper are historical, analysis, synthesis and empirical research conducted as a quantitative data analysis of a questionnaire distributed to people with disabilities on the sample of 200 disabled people from Croatia. The results of the research indicate that significant improvement should be implemented regarding suitable tourist offer in order to satisfy needs of tourists with different types of physical disabilities in Republic of Croatia. Based on the research results authors provide numerous recommendations to be implemented in Croatian tourist sites.